2022
DOI: 10.1021/acs.jafc.2c00942
|View full text |Cite
|
Sign up to set email alerts
|

Green Leaf Volatile Trans-2-Hexenal Inhibits the Growth of Fusarium graminearum by Inducing Membrane Damage, ROS Accumulation, and Cell Dysfunction

Abstract: Fusarium graminearum, the main agent of Fusarium head blight (FHB), can cause serious yield loss and secrete mycotoxins to contaminate grain. Here, the biological activity of trans-2-hexenal (T2H) against F. graminearum was determined and its mode of action (MOA) was investigated. Furthermore, surface plasmon resonance with liquid chromatography–tandem mass spectrometry (SPR-LC–MS/MS), bioinformatic analysis, and gene knockout technique were combined to identify the binding proteins of T2H in F. graminearum ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…These odorant substrates of HpGSTd1 were identified as the volatiles emitted from various plants. For example, trans -2-hexenal is a typical green leaf volatile that is usually released from damaged plants through the lipoxygenase pathway, , and trans , cis -2,6-nonadienal is a volatile compound of cucumber and chickasaw blackberry. , Cinnamaldehyde was identified from the volatiles of multiple plants, which included maize, which is the H. parallela host plant.…”
Section: Discussionmentioning
confidence: 99%
“…These odorant substrates of HpGSTd1 were identified as the volatiles emitted from various plants. For example, trans -2-hexenal is a typical green leaf volatile that is usually released from damaged plants through the lipoxygenase pathway, , and trans , cis -2,6-nonadienal is a volatile compound of cucumber and chickasaw blackberry. , Cinnamaldehyde was identified from the volatiles of multiple plants, which included maize, which is the H. parallela host plant.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of PSMs on P. capsici were evaluated according to a previous method with modifications (Ma et al, 2022). Briefly, a mycelial plug (5 mm diameter) of P. capsici was placed at the centre of a Petri dish containing V8 juice medium, and then PSM was added to the upper part of the sealed Petri dish.…”
Section: In Vitro Inhibitory Effects Of Psms On P Capsicimentioning
confidence: 99%
“…Zhu et al (2020) found that vitamin E had an indirect regulatory effect on the accumulation of vomitoxin (DON) in wheat [ 167 ]. Moreover, trans-2-hexenal, T2H, a typical green leaf volatile, synthesized from the primary metabolite linolenic acid or linoleic acid in plants, was proved to be a biofumigant for protecting crops against Fg [ 168 ]. Therefore, in the absence of resistant germplasm resources in wheat and with the scarcity of FHB-resistant strains with wide adaptability, the choice of chemical fungicides has become a common method of FHB control, but this is inevitably contrary to the concept of “advocating green production mode and promoting sustainable agricultural development”.…”
Section: Biological and Chemical Controlmentioning
confidence: 99%